Scientific word, Version 1.0. (1993) - Köksal Köksal, Semen Semen
Abstract : Scientific Word is the first fully integrated mathematical word processor in the Windows 3.1 environment, which uses the T E X typesetting language for output. It runs as a Microsoft Windows application program and has two-way interface to T E X . The Scientific Word is an object-oriented WYSIWYG word processor for virtually all users who need typesetting scientific books, manuals and papers. It includes automatic equation numbering, spell checking, and L A T E X and D V I previewer.